Meaning Analysis of ???? and ???? Emojis in Chat Apps: A Semiotic-Semantic Study - Yumeina, Fariha Faza; Nabila, Hana; Dewi, Lusiana Suciati (Ma'soem University, 2024)
This research discusses the meaning of ???? and ???? emojis in chat apps. The ???? emoji is often used to express sadness or frustration, while the ???? emoji is often used for dark humor or to express that something is so funny it's